Evidence Based Practice Senam Aerobic Low Impact Terhadap Penurunan Tanda dan Gejala Resiko Perilaku Kekerasan - Talasi, Neli Nilce; Karame, Verra (Yayasan Syalom Cipta Sumikolah, 2026)
The risk of violent behavior is an angry response manifested in the form of speaking with threatening words, carrying out actions that are dangerous to oneself, others, and the environment. The impact of violent behavior is a loss of self-control, harming oneself, others, and the environment. One nursing intervention that can be performed on patients at risk of violent behavior is low-impact aerobic exercise. Low-impact aerobic exercise is a gymnastics movement performed with a slow rhythm, meaning the movement is slower, with basic walking movements, one foot remaining on the floor, and no jumping movements at all. To determine the effectiveness of low-impact aerobic exercise on patients at risk of violence. A case study was used. Subjects were patients with mental disorders at risk of violence at Prof. VL. Ratumbuysang Hospital. Results: The study, using evidence-based nursing, found that low-impact aerobic exercise, performed three times a 24-hour period, reduced signs and symptoms of violent behavior, such as restlessness and pacing, irritability, and sharp and cynical speech. The results of the case study showed that after the intervention, Mrs. MA experienced a decrease in signs and symptoms of violent behavior. Recommendation: All healthcare workers should develop standard operating procedures (SOPs) for low-impact aerobic exercise, as it has many benefits, one of which is reducing signs and symptoms of violent behavior.